Behavior Change over Time When Driving with Adaptive Cruise Control. (September 2022) - Reagan, Ian J.; Cicchino, Jessica B.; Teoh, Eric R.; Reimer, Bryan; Mehler, Bruce; Gershon, Pnina
A field operational test assessed visual-manual disengagement when driving with adaptive cruise control (ACC) relative to manual driving. Ten volunteers drove instrumented vehicles on public roads for 4 weeks, using the vehicles as they would their own. To study change over time, the 4-week trial was divided evenly into two periods. Analyses were based on video of drives on limited-access highways when speed was above 25 mph. Visual-manual disengagement from driving was defined as periods when drivers had both hands off the steering wheel or performed visual-manual secondary activity with electronics. Odds of visual-manual disengagement increased from period 1 (weeks 1 and 2) to period 2 (weeks 3 and 4) more during ACC use than during manual driving. Conversely, odds of cellphone manipulation and hands-offwheel behavior increased in period 2 during manual driving only, suggesting a nuanced connection between behavioral adaptation to ACC use after a month of exposure.